Effect of cash dividends on market share price of firms listed in the Nairobi Securities Exchange - Micere, Antony Njogu (Strathmore University, 2021)
Shareholders invest by buying shares in particular organizations due to the benefits that their investments will bring, which is in form of capital gains or dividends such as cash dividends paid as interim or final dividends. The study deepens overall understanding of information content and signaling theory with specific focus on cash dividends. The objective of this study is to determine the effects of cash dividend paid on market share prices. The variables used to develop the study are interims and final cash dividends, market share price and control variables. The study took into consideration of all the firms listed in the Nairobi Securities Exchange from year 2009 to year 2019. Primary data and secondary data were used to provide valid and reliable findings. Primary data were collected directly from the businesses to determine the considerations made by firms before payment of dividends. Data was collected from primary sources by use of a questionnaire and also from secondary sources by review of annual reports and other disclosure documentations. Correlation research design involving descriptive statistics analysis was used to analyze and interpret the data. Findings from the study revealed that there is a positive and significant relationship between cash dividends paid and share market prices. The study established that listed firms consider several factors before payment of cash dividends. Findings from the study showed availability of cash as the main factor considered by organizations before payment of cash dividends. Other factors were also considered before cash dividends disbursements. The study concluded that the dividend payout of listed firms in the Nairobi Securities Exchange impacts share prices. The study recommends that listed firms should be keen on dividend payments they adopt during financial periods as the share price is influenced by the dividend pay-out made by the firm.
A Thesis submitted in partial fulfillment of the requirement for the Degree of Master of Commerce at Strathmore University
Keywords: Cash dividends; Market share price; Nairobi Securities Exchange